Etude de la résistance aux anticoccidiens utilisés en volaille - BOUDOUR , Djihane; HADDI , Soumia khadidja; BELGHOUL , Fatima zohra; BAKLI , Sabrina Encadrent (Université Sétif 1 Ferhat Abbas . Faculté des Sciences de la Nature et de la Vie, 2025)
Avian coccidiosis is a common and costly parasitic disease caused by protozoa of the genus Eimeria, which induce intestinal lesions, growth retardation, decreased production, and sometimes high mortality. Transmission occurs through ingestion of sporulated oocysts present in the environment. Two main classes of anticoccidial drugs are used to control this disease: synthetic chemical anticoccidials (such as diclazuril, toltrazuril, halofuginone, clopidol, and amprolium), which target parasite structures or metabolism; and natural ionophores (including monensin, salinomycin, narasin, and lasalocid), which disrupt ionic exchange in parasitic cells while promoting partial immunity. However, intensive use of these molecules has led to the emergence of resistance. Resistance to anticoccidials is defined as the parasite’s ability to survive despite normally effective doses. It can be acquired, cross, or multiple resistance, and results from several mechanisms such as genetic mutations, overexpression of ABC transporters, metabolic adaptation, or sexual recombination. Recent studies have identified specific mutations associated with resistance to various compounds. To address this challenge, alternative solutions are being explored, including live attenuated vaccines, plant extracts, essential oils, probiotics, as well as vitamins and minerals that enhance immunity. Sustainable control of coccidiosis thus relies on an integrated strategy combining hygiene, biosecurity, product rotation, vaccination, and natural alternatives.
Keywords: Coccidiose